Is minimally invasive plate osteosynthesis superior to open plating for fixation of two-part fracture of the proximal humerus?. (18th March 2019) - Kim, Young-Gun; Park, Kyeong-Hyeon; Kim, Joon-Woo; Oh, Jong-Keon; Yoon, Jong-Pil; Kim, Hee-June; Oh, Chang-Wug
Purpose: Displaced two-part fractures of the proximal humerus are generally treated with open plate (OP) fixation. Recently, minimally invasive plate osteosynthesis (MIPO) has been increasingly favored for fracture healing and functional recovery. We aimed to compare OP and MIPO for two-part fractures of the proximal humerus to identify outcome differences. Methods: All patients who underwent OP or MIPO for a displaced two-part fracture of the proximal humerus at a single level I trauma center between 2007 and 2013 were retrospectively evaluated. Of the patients, 17 were treated using the OP method through the delto-pectoral approach and 19 with MIPO through deltoid splitting. Radiographic results were evaluated to determine the union rate, time to union, and alignment. Functional outcomes were measured with Constant and UCLA scores. Radiation exposure and operative time were also evaluated. Results: All patients achieved bone union without complication. In the OP and MIPO groups, no significant difference was observed in the neck shaft angles, constant scores, or UCLA scores. The OP group required less radiation exposure time than the MIPO group ( p < 0.001). However, the OP group showed more operation time than the MIPO group ( p < 0.001). Conclusions: Both techniques showed satisfactory radiographic and functional outcomes in two-part fractures of the proximal humerus. Although MIPO technique offers advantages, including minimal soft tissue damage and short operation time, surgeons and patients should be warned of the invisible risk from the radiation hazard.